Blue light protection factor: a method to assess the protective efficacy of cosmetics against blue light-induced skin damage in the Chinese population - Zhang, Rui; Pu, Weilin; Zhang, Xinyuan; Di, Ye; Xu, Jing; Zhu, Meiyan; Tan, Yimei; Liu, Wei; Krutmann, Jean; Wang, Jiucun; Ma, Yanyun (Photochemical & photobiological sciences, 2024)
Background Previous studies have shown that visible light (VL), especially blue light (BL), could cause significant skin damage. With the emergence of VL protection products, a harmonization of light protection methods has been proposed, but it has not been widely applied in the Chinese population. Objective Based on this framework, we propose an accurate and simplified method to evaluate the efficacy of BL photoprotection for the Chinese population. Methods All subjects ( n = 30) were irradiated daily using a blue LED light for four consecutive days. Each irradiation dose was 3/4 MPPD (minimum persistent pigmentation darkening). The skin pigmentation parameters, including L * , M , and ITA°, were recorded. We proposed the blue light protection factor (BPF) metric based on the skin pigmentation parameters to evaluate the anti-blue light efficacies of different products. Results We found that the level of pigmentation rose progressively and linearly as blue light exposure increased. We proposed a metric, BPF, to reflect the anti-blue light efficacy of products based on the linear changes in skin pigment characteristics following daily BL exposure. Moreover, we discovered that the BPF metric could clearly distinguish the anti-blue light efficacies between two products and the control group, suggesting that BPF is an efficient and simple-to-use metric for anti-blue light evaluation. Conclusion Our study proposed an accurate and simplified method with an easy-to-use metric, BPF, to accurately characterize the anti-blue light efficacies of cosmetic products, providing support for further development of anti-blue light cosmetics.